2009
DOI: 10.2337/db08-0303
|View full text |Cite
|
Sign up to set email alerts
|

DOC2B: A Novel Syntaxin-4 Binding Protein Mediating Insulin-Regulated GLUT4 Vesicle Fusion in Adipocytes

Abstract: OBJECTIVE-Insulin stimulates glucose uptake in skeletal muscle and adipose tissues primarily by stimulating the translocation of vesicles containing a facilitative glucose transporter, GLUT4, from intracellular compartments to the plasma membrane. The formation of stable soluble N-ethyl-maleimidesensitive fusion protein [NSF] attachment protein receptor (SNARE) complexes between vesicle-associated membrane protein-2 (VAMP-2) and syntaxin-4 initiates GLUT4 vesicle docking and fusion processes. Additional factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
66
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 34 publications
9
66
0
Order By: Relevance
“…Double C2-like domains beta (DOC2B), a protein that contains two C2 domains, is localised to small punctate structures that are scattered throughout the cytoplasm in adipocytes; from these it translocates to the plasma membrane and binds to syntaxin-4 in response to insulin in a Ca 2+ -dependent manner. Reducing DOC2B levels by RNA interference impairs insulin-dependent glucose transport in adipocytes (Fukuda et al, 2009). C2 domains insert into membranes and promote membrane curvature, thus further aiding fusion (McMahon et al, 2010).…”
Section: Box 3 Gaps and Rabsmentioning
confidence: 99%
“…Double C2-like domains beta (DOC2B), a protein that contains two C2 domains, is localised to small punctate structures that are scattered throughout the cytoplasm in adipocytes; from these it translocates to the plasma membrane and binds to syntaxin-4 in response to insulin in a Ca 2+ -dependent manner. Reducing DOC2B levels by RNA interference impairs insulin-dependent glucose transport in adipocytes (Fukuda et al, 2009). C2 domains insert into membranes and promote membrane curvature, thus further aiding fusion (McMahon et al, 2010).…”
Section: Box 3 Gaps and Rabsmentioning
confidence: 99%
“…While the requirement of Ca 2C for Rip11 binding to acidic phospholipids has yet to be determined, in adrenal chromaffin cells, Doc2b is recruited to the cell surface in a Ca 2C -dependent manner where it functions as a priming factor and increases the number of fusion-competent vesicles (Groffen et al 2004, Friedrich et al 2008. A recent study in 3T3-L1 adipocytes has demonstrated that Doc2b is recruited to the plasma membrane in an insulinand Ca 2C -dependent manner where it associates with syntaxin4 (Fukuda et al 2009). The recruitment of Doc2b was found to be necessary for GLUT4 vesicle fusion as both a mutant deficient in Ca 2C binding and the siRNA-mediated depletion of Doc2b from adipocytes inhibited insulinstimulated glucose uptake (Fukuda et al 2009).…”
Section: Protein Complexes Involved In Docking and Fusion Of Glut4 Vementioning
confidence: 99%
“…A recent study in 3T3-L1 adipocytes has demonstrated that Doc2b is recruited to the plasma membrane in an insulinand Ca 2C -dependent manner where it associates with syntaxin4 (Fukuda et al 2009). The recruitment of Doc2b was found to be necessary for GLUT4 vesicle fusion as both a mutant deficient in Ca 2C binding and the siRNA-mediated depletion of Doc2b from adipocytes inhibited insulinstimulated glucose uptake (Fukuda et al 2009).…”
Section: Protein Complexes Involved In Docking and Fusion Of Glut4 Vementioning
confidence: 99%
See 1 more Smart Citation
“…Binding of calcium to DOC2B significantly increases its affinity toward phospholipids, leading to translocation of proteins from the cytosol to plasma membrane (8). Recently, DOC2B was shown as a posi-tive SNARE regulator for GLUT4 vesicle fusion and mediates insulin-stimulated glucose transport in adipocytes as well as a regulator for delayed insulin secretion in MIN6 cells (9). It is involved in the deformation of synaptic membranes during synaptic vesicle exocytosis (10,11).…”
mentioning
confidence: 99%